Digital Communication Approaches to Strengthen Public Trust and Engagement - Adzimah, Maulidatul; Yaqin, Muhammad Ainul (Journal of Educational Management Research, 2024)
Advances in information technology have brought significant changes in the way educational institutions interact with the community. Madrasahs utilize digital communication strategies to build public trust and improve the image of the institution. This study aims to analyze the digital communication strategies implemented by Islamic high schools in strengthening public trust through transparency and honesty in conveying information. This study uses a descriptive qualitative approach with data collection methods through observation, interviews, and documentation. The subjects of the study included the principal, deputy head of public relations, students, and parents of students. The focus of this study is how digital communication is used as a strategy to build closer relationships with the community and increase the level of public participation and involvement in the madrasah. The results of the study show that madrasahs implement various digital communication strategies, such as the use of social media, official websites, and audiovisual-based information publications to increase transparency and public trust.